Socialization of Cash Waqf Literacy as a Waqf Solution For Millennial Generation Students in Kulon Progo Regency - Ifan Agung Pambudi; Hediantoro Hediantoro; Dita Widyaningrum; Rizky Surya Saputra; Nafis Sholikhah; Aulia Nurul Safitri; Febrian Yena Remalia; Chilmi Syafiq Mashum; Choirul Arifah; Mellyana Alvi Purniaji; Fikri Anam; Sakina Tulaulia; Shafa Yulita Salma Nafisa; Nurul Imtiqomah (Journal of Islamic Economy and Community Engagement, 2022)
The socialization entitled "Awareness of Cash Waqf Literacy as a Waqf Solution for Millennials in Kulon Progo Regency Students" aims to broaden insights about cash waqf and how to make a cash waqf so that it is expected to generate interest in cash representation. The method of carrying out cash waqf literacy socialization activities uses lecture and discussion methods. The socialization was held in the meeting room of the Kulon Progo Tourism Office at 17.00 West Indonesia Time with 45 participants consisting of members of the Kulon Progo Student Association (IMKP). The results of this cash waqf socialization is to provide knowledge about cash waqf as a solution for giving to young people who provide ease of speaking in this 4.0 era.Keywords: socialization, millennials, cash waqf.